African perspective on the crisis of global capitalism - Dembele, Demba Moussa (Ciência & Trópico, 2013)
ABSTRACTThis paper argues that the collapse of market fundamentalism with the financial crisis of 2008 is a further sign of the systemic crisis of global capitalism whose legitimacy is being questioned in even western countries. This is why some are calling it a “crisis of civilization”, the civilization associated with the birth and rise of capitalism. One aspect of the crisis is the weakening of western economic and political hegemony in the world, with challenges from emerging blocs in the South, such as the BRICS and CELAC, among others. Another important aspect of the crisis of legitimacy of global capitalism is the discredit of mainstream thinking on development, which is in large part the work of intellectuals, researchers and social movements from the Global South. In this regard, the paper underlines the contribution of African intellectuals, research institutions and social movements by analyzing the role of some leading African research institutions, like CODESRIA, Third World Forum, and intellectuals, like Samir Amin and others. The paper concludes by showing that challenges to the mainstream thinking on development are giving way to new conceptions of development, such as “Buen Vivir” Latin America and “Gross National Happiness” in Asia. Socialism in the 21st Century.KEYWORDS: Capitalism. Fundamentalism. Crisis. Development. Legitimacy. BRICS. CELAC.Perspectiva africana sobre a crise do capitalismo globalRESUMOEste artigo argumenta que o colapso do fundamentalismo de mercado com a crise financeira de 2008 é mais um sinal da crise sistêmica do capitalismo global, cuja legitimidade é questionada até mesmo em países ocidentais. É por isso que alguns estão chamando de uma «crise de civilização», a civilização associada com o nascimento e ascensão do capitalismo. Um aspecto da crise é o enfraquecimento da hegemonia econômica e política ocidental no mundo, com desafios de blocos emergentes do Sul, como os BRICS, CELAC, entre outros. Outro aspecto importante da crise de legitimidade do capitalismo global é o descrédito do pensamento dominante sobre o desenvolvimento, que é, em grande parte o trabalho, de intelectuais, pesquisadores e movimentos sociais do Sul Global. A esse respeito, o documento sublinha a contribuição dos intelectuais africanos, instituições de pesquisa e movimentos sociais, analisando o papel das instituições africanas líderes de pesquisa, como CODESRIA, Fórum do Terceiro Mundo, e dos intelectuais, como Samir Amin e outros. O artigo conclui mostrando que os desafios para o pensamento dominante sobre o desenvolvimento estão dando lugar a novas concepções de desenvolvimento, tais como “Buen Vivir” América Latina e “Felicidade Nacional Bruta”, na Ásia.PALAVRAS-CHAVE: Capitalismo. Fundamentalismo. Crise. Desenvolvimento. Legitimidade. BRICS. CELAC.